Presenting the Pauline Voice: An Appreciation of the Letter to the Laodiceans - Longenecker, Bruce W. (New Testament studies, 2016)
It is commonly thought that the apocryphal Letter to the Laodiceans was composed by an author who was little more than an editor, piecing together phrases from Pauline texts in a mediocre fashion. Not only does the text seem devoid of conceptual rigour and theological merit, but it is also thought to lack a coherent structure. This essay proposes that, to the contrary of most estimates, the Letter to the Laodiceans exhibits a discernible structural coherence from which a rhetorical strategy is evident.